Non-NMDA Mechanisms of Analgesia in Ketamine Analogs - Voss, Logan J.; Harvey, Martyn G.; Sleigh, James W. (Frontiers in Pain Research, 2022)
Despite 50 years of clinical use and experimental endeavor the anesthetic, analgesic, and psychomimetic effects of ketamine remain to be fully elucidated. While NMDA receptor antagonism has been long held as ketamine's fundamental molecular action, interrogation of bespoke ketamine analogs with known absent NMDA binding, yet profound anesthetic and analgesia fingerprints, suggests alternative targets are responsible for these effects. Herein we describe experimental findings utilizing such analogs as probes to explore ketamine-based analgesic molecular targets. We have focused on two-pore potassium leak channels, identifying TWIK channels as a rational target to pursue further. While the totality of ketamine's mechanistic action is yet to be fully determined, these investigations raise the intriguing prospect of separating out analgesia and anesthetic effects from ketamine's undesirable psychomimesis—and development of more specific analgesic medications.